PENGARUH PROGRAM JAWS TERHADAP KEMAMPUAN MENGETIK PADA TUNANETRA DI PSBN TUAH SAKATO PADANG - Safaruddin, Markis Yunus, Elsa Efrina (Universitas Negeri Padang, 2013)
: This research is motivated by the problems faced by visually impaired clients in the preparation classes PSBN Tuah Sakato Padang, the ability of a computer typing is very minimal. This type of research is a Quasi Experiment, pretest-posttest design the experiments carried out on one group without using the comparison group. The subjects were four visually impaired clients in the preparation classes PSBN Tuah Sakato Padang. Data obtained using the test works. Analysis of the data used is the Mann-Whitney test for hypothesis testing criteria acceptable if Uhit> UTab and conditions beyond the hypothesis is rejected at the 95% significance level or α = 0.05 level. The results of data processing show UTab Uhit = 0.5 and = 0, meaning that the hypothesis is accepted. So the results showed that the JAWS program effect on the ability to type on a blind preparation classes in PSBN Tuah Sakato Padang. Therefore, it is suggested in the social institutions in order to always provide education about technology especially computers so that children are more confident and are not afraid of technology.